Performance Of Integrated Energy Recovery For Split Unit Air-Conditioning System In Hot And Humid Environment - Tang, Chiau Yong (2018)
The escalating energy consumption in conditioning fresh air causes abundance of condensing heat energy wasted especially under the hot and humid climate. In this context, by installing energy recovery unit, thermal energy is transferred from outgoing to incoming air streams which recovers the wasted energy. The main objectives of this research are to evaluate the performance of stand-alone energy recovery unit and split unit air-conditioning system, to assess the performance of integrated system and to compare the performance between stand-alone air-conditioning unit and integrated system by varying parameters of temperature of 28ºC, 31ºC, 34ºC and 40ºC, relative humidity of 65%, 75% and 85% as well as air-velocity of 1 ms-1, 2 ms-1 and 3 ms-1.